Assessment of heavy metals concentration in airborne particulate matter (PM₁₀) in selected traffic areas of the Klang Valley, Malaysia - Elawad, Rasheida Elawad Elhadi (2017)
In recent years the level of heavy metals in the atmospheric particulate matter in traffic areas has been of considerable concern. This study was conducted to assess the heavy metals concentration in airborne particulate matter (PM10) in selected traffic areas of Klang Valley. The PM10 samples was collected at four different areas with three sampling sites with different traffic densities (high, medium and low) during the Southwest and Northeast monsoon from June 2014 to January 2015. The PM10 samples were collected by High Volume Sampler (HVS) using glass fibre filter. The Heavy metals in PM10 were assessed with inductively coupled plasma mass spectrometry (ICP-MS). Multivariate statistics using Cluster Analysis (CA) and Principal Component Analysis (PCA) were used in source identification. Also AERMOD dispersion model was used to simulate PM10 and heavy metals. The finding from this study revealed differences in the mean concentration of PM10 between seasons and different traffic density sites. During the Southwest monsoon, Shah Alam recoded the highest mean concentrations for the high, medium and low traffic density sites with 210.14, 171.74 and 111.56 μg/ m3 respectively. The results recorded for the high and medium traffic sites by far exceeded the standard of 150.0 μg/ m3 of Recommended Malaysian Air Quality Guidelines (RMAQG). For the Northeast monsoon season Shah Alam recorded the highest mean concentation (139.28 μg/ m) for high traffic density sites, while Cheras recorded the highest mean concentration of (121.11 and 45.68 μg/ m3) for medium and low traffic density sites respectively. As for the heavy metals the findings showed differences in concentration of heavy metals between seasons and traffic density sites as well. The heavy metals concentration was below the limit of concentration set by both United States Environmental Protection Agency (USEPA) and World Health Organization (WHO except for Arsenic (As). The finding from CA and PCA identified vehicle exhaust emission, non-exhaust emission (brake wear, tire wear and re-suspension dust) and heavy lubricating oil combustion as major sources of PM10 and heavy metals. The AERMOD model simulation revealed that the maximum concentrations of PM10 and heavy metals were observed in central, southeast, southwest and west of the model domain. The validation of the AERMOD model performed well in simulating PM10 and most of the heavy metals. Owing to the effects of PM10, which is associated with health risks, the level of PM10 and its heavy metals content, especially Arsenic (As), should be monitored frequently to achieve a healthy environment in the study area.